Factors associated with unintended pregnancy in Brazil: cross-sectional results from the Birth in Brazil National Survey, 2011/2012 - Mariza Miranda Theme-Filha; Marcia Leonardi Baldisserotto; Ana Claudia Santos Amaral Fraga; Susan Ayers; Silvana Granado Nogueira da Gama; Maria do Carmo Leal (BMC, 2016)
Abstract Background Unintended pregnancy, a pregnancy that have been either unwanted or mistimed, is a serious public health issue in Brazil. It is reported for more than half of women who gave birth in the country, but the characteristics of women who conceive unintentionally are rarely documented. The aim of this study is to analyse the prevalence and the association between unintended pregnancy and a set of sociodemographic characteristics, individual-level variables and history of obstetric outcomes. Methods Birth in Brazil is a cross-sectional study with countrywide representation that interviewed 23,894 women after birth. The information about intendedness of pregnancy was obtained after birth at the hospital and classified into three categories: intended, mistimed or unwanted. Multinomial regression analysis was used to estimate the associations between intendedness of a pregnancy, and sociodemographic and obstetric variables, calculating odds ratios and 95 % confidence intervals. All significant variables in the bivariate analysis were included in the multinomial multivariate model and the final model retaining variables that remained significant at the 5 % level. Results Unintended pregnancy was reported by 55.4 % of postpartum women. The following variables maintained positive and significant statistical associations with mistimed pregnancy: maternal age < 20 years (OR = 1.89, 95 % CI: 1.68-2.14); brown (OR = 1.15, 95 % CI: 1.04-1.27) or yellow skin color (OR = 1.56, 95 % CI: 1.05-2.32); having no partner (OR = 2.32, 95 % CI: 1.99-2.71); having no paid job (OR = 1.15, 95 % CI: 1.04-1.27); alcohol abuse with risk of alcoholism (OR = 1.25, 95 % CI: 1.04-1.50) and having had three or more births (OR = 2.01, 95 % CI: 1.63-2.47). The same factors were associated with unwanted pregnancy, though the strength of the associations was generally stronger. Women with three or more births were 14 times more likely to have an unwanted pregnancy, and complication in the previous pregnancies and preterm birth were 40 % and 19 % higher, respectively. Previous neonatal death was a protective factor for both mistimed (OR = 0.61, 95 % CI: 0.44-0.85) and unwanted pregnancy (OR = 0.44, 95 % CI: 0.34-0.57). Conclusions This study confirms findings from previous research about the influence of socioeconomic and individual risk factors on unintended pregnancy. It takes a new approach to the problem by showing the importance of previous neonatal death, preterm birth and complication during pregnancy as risk factors for unintended pregnancy.